2005
DOI: 10.1021/bi048025o
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Mutagenesis of Insulin. Foldability and Function Are Inversely Regulated by a Stereospecific Switch in the B Chain,

Abstract: How insulin binds to its receptor is unknown despite decades of investigation. Here, we employ chiral mutagenesis-comparison of corresponding D and L amino acid substitutions in the hormoneto define a structural switch between folding-competent and active conformations. Our strategy is motivated by the T R transition, an allosteric feature of zinc-hexamer assembly in which an invariant glycine in the B chain changes conformations. In the classical T state, Gly B8 lies within a -turn and exhibits a positive ϕ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
124
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(132 citation statements)
references
References 78 publications
7
124
1
Order By: Relevance
“…Dihedral angles of GlyB8 range from positive in the T-state (56.4 6 4.1) to negative in the R-state (À63.0 6 3.12). 32 Dihedral angles of GlyB8 in 4SS-insulin were found to be positive and similar to those observed in the T-state (46.2 and 42.4 for the two molecules in the asymmetric unit). Furthermore, the CD spectroscopy results show no changes in CD spectra upon phenol titration, suggesting no or only very limited changes in the ''hinge'' region.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Dihedral angles of GlyB8 range from positive in the T-state (56.4 6 4.1) to negative in the R-state (À63.0 6 3.12). 32 Dihedral angles of GlyB8 in 4SS-insulin were found to be positive and similar to those observed in the T-state (46.2 and 42.4 for the two molecules in the asymmetric unit). Furthermore, the CD spectroscopy results show no changes in CD spectra upon phenol titration, suggesting no or only very limited changes in the ''hinge'' region.…”
Section: Discussionsupporting
confidence: 69%
“…Previously, it was also suggested that reorganization of the Nterminal end of the B-chain, such as the transition from T-state to R-state, is necessary for the insulin receptor binding. 32 Our results demonstrate for the first time that structural flexibility of the N-terminal end of the B-chain of insulin is not a prerequisite for binding and that an insulin analog not capable of forming the classical R-state is fully active. Since the first four amino acids of the B-chain do not have a large affect on insulin interaction with the insulin receptor, 42,43 the ''functional'' difference between the T-state and the R-state lies around the GlyB8 ''hinge'' region.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Because B8 glycine has a positive (Phi) dihedral angle (forbidden for L-amino acids), the presence of L-serine at B8 requires a reorientation of B8 conformation to accommodate its side chain, which results in rotation of B1-B8, turning the B7 cysteine away from its intended partner at A7. This change is reflected in lowered thermodynamic stability of the insulin molecule and significantly impairs yields in chain recombination experiments (24,25). On the basis of these and other observations, Nakagawa et al (24) have suggested that ''the correct B8 conformation plays a critical role in the mechanism of disulfide pairing'' during insulin biosynthesis and when substituted may ''kinetically block the formation of the A7-B7 disulfide bridge.''…”
Section: Discussionmentioning
confidence: 99%
“…This change is reflected in lowered thermodynamic stability of the insulin molecule and significantly impairs yields in chain recombination experiments (24,25). On the basis of these and other observations, Nakagawa et al (24) have suggested that ''the correct B8 conformation plays a critical role in the mechanism of disulfide pairing'' during insulin biosynthesis and when substituted may ''kinetically block the formation of the A7-B7 disulfide bridge.'' Similar considerations apply to B23 glycine where L-amino acid substitutions would likely disrupt normal folding of the peptide chain near the critical A20-B19 disulfide bridge (26).…”
Section: Discussionmentioning
confidence: 99%